Design and testing of piezoelectric energy harvesting devices for generation of higher electric power for wireless sensor networks - Zhu, Meiling; Worthington, Emma (Cranfield University, 2009)
This paper reports our design and testing results on the electric output performance of a vibration-based piezoelectric energy harvesting device (PEHD). The PEHD is a cantilever with a sandwich structure and seismic mass attached to the tip. The geometric parameters of the device are based on optimization design with a volume of around 1cm3 and at a targeted resonant frequency of 80-100 Hz. A maximum output power of 370μW at 15.5 volts into a 325kΩ resistive load is generated at the resonant frequency of 87Hz and under an acceleration of 0.23g. Quite remarkably, this power is a very encouraging power figure that gives the prospect of being able to power a wider range of applications than is currently possible in wireless sensor networ
Keywords: piezoelectric energy harvesting